THE UK NATURAL GAS MARKET AND THE THEORY OF STORAGE - Preziosi, Davide (2010)
ABSTRACT This dissertation analyses the UK natural gas market through the lens of the Theory of Storage. Unlike other storable commodities, natural gas does not corroborate conventional theory due to its particular storage characteristics and key role in power generation. Particular emphasis is given to the estimation of convenience yield, its determinants, and the month-of-the-year effect. Natural gas prices volatility and its relationship with storage levels is also estimated by means of a “unified test” of the theory of storage in an ARMAX-asymmetric GARCH model framework. The findings are not supportive of the theory of the storage due to market technicalities leading market participants to aggressively accumulate natural gas on the spot market before periodic maintenance work on the two interconnectors linking the UK to the continent in September. A third analysis investigates the response of future prices to spot price changes according to different levels of storage. The test does not support previous empirical analysis due to the relative inflexibility of gas supply. A fourth analysis explores the presence of risk premium and its determinants. I argue the case that thanks to the process of liberalization the UK natural gas market would resemble more the US in the sense that future prices will incorporate a positive premium reflecting the increasing hedging concern of suppliers to sell their inventories at a profitable price.